An Uncommon Variation of the Superior Laryngeal Artery - Samereh Dehghani-Soltani; Seyed Hassan Eftekhar-Vaghefi; Abdolreza Babaee (Negah Institute for Scientific Communication, 2016)
This case study reports a rare variation of the superior laryngeal artery (SLA), which is the principal arterial supply of the larynx. The knowledge of the arterial variations is essential for the surgeons to prevent blood loss and postoperative complications. During routine dissection of an adult male cadaver, a rare arterial variation in the SLA was seen. In this case, the SLA passed through the thyroid foramen. The present study provides significant information about the SLA. We hope that it helps describe the arterial bleeding that may happen during laryngeal surgery.